1999
DOI: 10.1002/(sici)1520-6777(1999)18:6<567::aid-nau7>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Leaking urine: Prevalence and associated factors in Australian women

Abstract: The Women's Health Australia project provided the opportunity to examine the prevalence of leaking urine and associated variables in three large cohorts of Australian women 18–23 years of age (“young” N = 14,761), 45–50 (“mid‐age” N = 14,070), and 70–75 (“older” N = 12,893). The proportion of women reporting leaking urine was 12.8% (95% CI: 12.2–13.3), 36.1% (35.2– 37.0), and 35% (34.1– 35.9) in each of the three cohorts, respectively. Logistic regression analysis showed significant associations between leakin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
2
16

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(131 citation statements)
references
References 27 publications
8
105
2
16
Order By: Relevance
“…A number of crosssectional studies have also found a significant association between BMI and incontinence, but have not distinguished between symptoms of stress or urge incontinence. 12,13,16,17 Although BMI has been most closely linked with stress incontinence, only a handful of studies have shown an association with urge incontinence in women. 8,15,35 In this study, the raised risk of urge incontinence was only restricted to women who were obese at the age 36 and 43 years and was considerably attenuated in the fully adjusted model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of crosssectional studies have also found a significant association between BMI and incontinence, but have not distinguished between symptoms of stress or urge incontinence. 12,13,16,17 Although BMI has been most closely linked with stress incontinence, only a handful of studies have shown an association with urge incontinence in women. 8,15,35 In this study, the raised risk of urge incontinence was only restricted to women who were obese at the age 36 and 43 years and was considerably attenuated in the fully adjusted model.…”
Section: Discussionmentioning
confidence: 99%
“…11 It was the first prospective study to show that childhood enuresis was associated with urge incontinence at 48 years of age (regular bedwetters at age 6 years had twice the risk) than the remaining sample. 11 Studies that have identified a relationship between higher body weight in midlife and incontinence have been either cross-sectional [12][13][14][15][16][17][18] or short-term studies. [19][20][21][22] Obesity, particularly in the abdominal area, may cause incontinence through increased intra-abdominal pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Chiarelli et al 17 found a 36% prevalence of any self-reported leakage during the past year among 14,070 Australian women aged 45 to 50 years. In a review of 13 general population studies, Hunskaar et al reported a 30% to 40% prevalence of incontinence among middle-aged women.…”
Section: Commentmentioning
confidence: 99%
“…Our findings are comparable to the SWAN study, which found a 62% (95% CI 31% -101%) increased risk of any leakage in parous women compared with nulliparous women aged 42-52 years. 9 In the Women's Health Australia project, Chiarelli et al 17 observed similar odds of leaking urine among women with one childbirth (adjusted OR=1.58, 95% CI 1.29-1.93) and women with two childbirths (adjusted OR=1.81, 95% CI 1.54-2.12). Additionally, as expected, 8 the odds ratios in these younger women were somewhat higher than those we had found in our cohort of older nurses.…”
mentioning
confidence: 99%
“…1,5,13,25,26 Procedures Institutional review board (IRB) approval was obtained from the University of North Carolina at Chapel Hill IRB for this study and the procedures are more fully described in a recent publication. 18 Twenty six elementary schools were selected from the 152 elementary schools in Taipei by using the systematic sampling method with pps and a second stage simple random sampling of 20 female teachers in each school was conducted.…”
Section: Measurementmentioning
confidence: 99%